RANCANG BANGUN SISTEM OTOMATIS DAN MONITORING JARAK JAUH ENGINEERING WORK STATION DI PLTU VIA WEB - Suryanto Suryanto; Edy Kurniawan (KOMPUTEK, 2020)
The engineering work station room is a server room that has a function to be the control center for all components in the PLTU which will have to be equipped with several sensors, namely the DHT11 temperature sensor, ZMPT101 voltage sensor, ACS712 current sensor to help keep temperature, voltage, current stable . To obtain maximum results, several stages are needed in designing this tool, including literature study, technical data collection, planning process, manufacturing, testing, discussion and conclusions.To maintain the conditions in the engineering work station room, an automatic system and remote monitoring were designed which have a working principle, namely if the temperature in the EWS room is below 18C then the AC motor is off. If the EWS room temperature is at 18C - 23C, the AC motor has a medium start. If the EWS room temperature is above 23C, the AC motor has full power. Meanwhile, the results of reading conditions in the EWS room, namely the conditions of temperature, voltage, and current will be displayed via the Thingspeak web. The results of this study the tool is able to work according to predetermined working principles and data analysis is also in accordance with existing calculations